INTERMAG Asia 2005. Digests of the IEEE International Magnetics Conference, 2005. 2005
DOI: 10.1109/intmag.2005.1463451
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate effects in soft CoFe films

Abstract: We report on growth rate effects in sputter-deposited CoFe films prepared using high target utilization sputtering technology (HiTUS). We find that the grain structure of these polycrystalline films is closely related to the growth rate. By changing the growth rate, samples were prepared with different grain structure, which in turn had the effect of changing the magnetic properties of the films. We demonstrate control of the coercivity, which varied by a factor of more than ten. This was achieved via grain si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A highly influential control mechanism of magnetism in thin films is also the actual process of thin film coating, together with the choice of deposition parameters. In the case of magnetic thin films fabricated via plasma sputtering, it has been shown that the deposition rates [25,26], substrate temperature, bias voltage, plasma power, base pressure and process gas pressure have a significant effect on the final magnetic thin film's properties. The list of controllable parameters of magnetic thin films is further complicated when one attempts to deposit flexible magnetic thin films.…”
Section: Introductionmentioning
confidence: 99%
“…A highly influential control mechanism of magnetism in thin films is also the actual process of thin film coating, together with the choice of deposition parameters. In the case of magnetic thin films fabricated via plasma sputtering, it has been shown that the deposition rates [25,26], substrate temperature, bias voltage, plasma power, base pressure and process gas pressure have a significant effect on the final magnetic thin film's properties. The list of controllable parameters of magnetic thin films is further complicated when one attempts to deposit flexible magnetic thin films.…”
Section: Introductionmentioning
confidence: 99%